Midlife Cardiovascular Status and Old Age Physical Functioning Trajectories in Older Businessmen - von Bonsdorff Mikaela; Haapanen Markus J; Törmäkangas Timo; Pitkälä Kaisu H; Stenholm Sari; Strandberg Timo E (Blackwell Publishing Inc., 2022)
OBJECTIVES: The associations between cardiovascular disease (CVD) risk and later physical functioning have been observed, but only a few studies with follow-up into old age are available. We investigated the association between cardiovascular status in midlife and physical functioning trajectories in old age.
DESIGN: Prospective cohort study.
SETTING: Helsinki Businessmen Study.
PARTICIPANTS: We studied white men born between 1919 and 1934 in the Helsinki Businessmen Study (HBS, initial n = 3490).
MEASUREMENTS: Three CVD status groups were formed based on clinical measurements carried out in 1974: signs of CVD (diagnosed clinically or with changes in ECG, chronic disease present or used medication, n = 563); healthy and low CVD risk (n = 593) and high CVD risk (n = 1222). Of them, 1560 men had data on physical functioning from at least one of four data collection waves between 2000-2010. Ten questions from the RAND-36 (SF-36) survey were used to construct physical functioning trajectories with latent class growth mixture models. Mortality was accounted for in competing risk models.
RESULTS: A five-class solution provided the optimal number of trajectories: “intact,” “high stable,” “high and declining,” “intermediate and declining,” and “consistently low” functioning. Compared with low CVD risk, high CVD risk in midlife decreased the risk of being classified into the intact (fully adjusted β = −3.98; standard error = 2.0; P =.046) relative to the consistently low physical functioning trajectory. Compared with low CVD risk, those with signs of CVD were less likely to follow the intact, high stable, or high and declining relative to the consistently low trajectory (all P <.018).
CONCLUSION: Among businessmen, a more favorable CVD profile in midlife was associated with better development of physical functioning in old age.